1980
DOI: 10.1111/j.1471-4159.1980.tb09653.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of GABA Metabolism in Discrete Rabbit Brain Regions under Methoxypyridoxine—Regional Differences in Cofactor Saturation and the Preictal Activation of Glutamate Decarboxylase Activity1

Abstract: The activities of the enzymes of the GABA system, glutamate decarboxylase (GAD) and GABA‐transaminase, were measured in discrete regions of the rabbit brain before the onset and during the course of sustained epileptiform seizures induced by the vitamin B6, analogue methoxypyridoxine (MP). GAD activities were measured in a reaction mixture alternatively containing the cofactor pyridoxal‐5′‐phosphate (PLP) in excess or containing no PLP (holoenzyme of GAD). A comparison between these two estimations showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

1980
1980
2005
2005

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 62 publications
2
18
0
1
Order By: Relevance
“…Indeed, regional differences in the fraction of GAD that is bound to PLP led to the initial suggestions that two forms of GAD exist (Nitsch, 1980;Itoh and Uchimura, 1981;Denner and Wu, 1985).…”
Section: Is Gad Preferentially Expressed In Phasically Firing Neurons?mentioning
confidence: 98%
“…Indeed, regional differences in the fraction of GAD that is bound to PLP led to the initial suggestions that two forms of GAD exist (Nitsch, 1980;Itoh and Uchimura, 1981;Denner and Wu, 1985).…”
Section: Is Gad Preferentially Expressed In Phasically Firing Neurons?mentioning
confidence: 98%
“…Our studies have shown that MP, probably in its phosphorylated form, competitively displaces pyridoxal phosphate from its binding sites at the protein component of the GABA-synthesizing enzyme glutamate decarboxylase (Nitsch, 1980). Glutamate decarboxylase inhibition reaches its peak before the onset of the seizures (Nitsch, 1980), resulting in a substantial decrease in the content of the inhibitory transmitter GABA , especially in GABA-rich brain centres (Nitsch & Okada, 1976). The already preictally significant drop in GABA content can be interpreted as at least one of the factors giving rise to the seizure (Nitsch & Okada, 1976).…”
Section: Introductionmentioning
confidence: 97%
“…The antagonistic preictal behavior of taurine and GABA is discussed with respect to synthesis, uptake from the blood, and antiepileptic properties. Key Words: Epileptic Since methoxypyridoxine, as a vitamin B6 analogue, was expected to be a potent inhibitor of the glutamate decarboxylase (GAD) activity, previous biochemical studies have focused on the dramatic increase in y-aminobutyric acid (GABA) content taking place before the appearance of generalized seizures (Nitsch and Okada, 1976) and the activity of related enzymes (Nitsch, 1980). Apart from a preliminary communication on the preictal increase in taurine level , other relevant amino acids have been virtually neglected.…”
mentioning
confidence: 99%